Household Behaviour towards Personal Care Products: A Comparative Study of Rural and Urban Mizoram (Global Journal of Management and Business Research, 2014)
The present study tries to highlight the behaviour of households as a consumer unit with a view to make a coherent analysis of the factors influencing the purchase of personal care items i.e. toothpaste, bath soap, hair oils/creams and body lotions. 640 households were sampled for the study from rural and urban areas covering all the functioning 8 districts of Mizoram. Promotion was found to be the most prominent factor triggering purchase behaviour among the respondents, followed by price and health benefits of the product.
Keywords: consumers; households; rural; urban; toothpaste; bath soap; hair oil/cream; body lotion